Testing the Usability of the MediCare System - et.al, Sarmad Monadel Sabree Al-Gayar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Smartphones, digital medical devices, smart bracelets, and mobile applications have emerged in the healthcare field as an effective way to help in the treatment of patients. Healthcare services are characterized by ease of use, low cost, accessibility, mobility, and reliability. The MediCare system was built to enhance healthcare services in the Iraqi environment. The MediCare system can run on smartphones or tablets that operate on Android, but it can also be used as a web application. The research team wanted to evaluate if the platform meets customers’ needs. Therefore, a usability survey for the MediCare system in regard to healthcare services and underlying technology was done. In this paper, an evaluation and usability measurement of the MediCare system is presented. The quantitative research shows that users found that the system is suitable for their needs. The system is especially necessary now, when the COVID-19 pandemic is a global emergency.